Restoration of the pre-Jurassic paleogeomorphology and its control on hydrocarbon distribution in western Ordos Basin - Yuan, Hui; Yin, Shuai; Dong, Li; Tan, Chengqian (Energy Geoscience, 2022)
In recent years, the discovery of the Jurassic oil reservoirs in the Western Thrust Belt of the Ordos Basin reveals that the Jurassic formation in this area has huge oil and gas potential. The pre-Jurassic paleogeomorphology plays a vital role in the formation of the Jurassic oil reservoirs. In this paper, the impression method is applied to restore the pre-Jurassic paleogeomorphology of the Hongde area in the western Ordos Basin, using a large number of drilling, logging, well testing and the latest 3D seismic data. The pre-Jurassic paleogeomorphological units in the study area can be categorized into five groups, including ancient channel valley, ancient terrace, slope, interchannel mound, and low residual mound facies. The oil reservoirs are mainly distributed in highland areas such as slope belts and low residual mounds, the main areas where hydrocarbons accumulate. In addition, the branch ditches in the study area are developed to the southeast and merged into the Ganshan ancient channel. The sandstone in the confluence area of the branch gully is well sorted and connected under frequent scouring by the river. The sand bodies of good connectivity therefore form a drainage system for long-term hydrocarbon migration. The formation of the Jurassic reservoirs in the study area is mainly affected by sedimentary facies, deposition location, and hydrocarbon migration pathway (or fault) of pre-Jurassic paleomorphology. The results from this study can be useful for the prediction of the Jurassic sweet spots in the western margin of the Ordos Basin. [Display omitted] •Impression method used to restore the pre-Jurassic paleogeomorphology in Hongde area.•Application of drilling, logging, well testing and latest 3D seismic data.•Results useful for the prediction of the Jurassic sweet spots.